DETERMINING SEDIMENTARY MATERIAL SOURCES IN A BRAZILIAN URBAN LAKE USING Zn STABLE ISOTOPE COMPOSITIONS OF BOTTOM SEDIMENTS: A PRELIMINARY STUDY - Araújo, Daniel Ferreira; Boaventura, Geraldo Resende; Mulholland, Daniel Santos; Garnier, Jeremie; Machado, Wilson; Babinski, Marly; Dantas, Elton Luiz (Geochimica Brasiliensis, 2020)
Zinc isotopes ratios provide qualitative and quantitative information about contributions from different Zn sources in the environment. Here we present the results of a preliminary study to identify the main sources controlling Zn isotope signatures of sediments from Lake Paranoá (Brazil), an urban water reservoir. The Zn isotope ratios were measured by MC-ICP-MS and expressed as δ66/64Zn notation relative to the JMC 3-0749-L solution. The studied sediments showed a narrow isotopic range (+0.00 to +0.13 ‰; n = 10) similar to that reported for intensely weathered soils worldwide (from -0.4 to +0.2‰). The geoaccumulation index (Igeo) also suggests low or negligible influence of Zn anthropogenic source. This research provides a baseline assessment of the Zn isotopes signatures in lake sedimentary environments under the influence of these weathered soils.